Wittgenstein's Challenge: The Impossibility of a Private Language - Pikri, Zainal (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2023)
The feasibility of a private language, a concept previously entertained by philosophers like Locke and Russell, is rigorously disputed by Wittgenstein in his later works. This article critically examines Wittgenstein’s standpoint on the notion of a private language, with a specific focus on its plausibility. It meticulously investigates the five arguments proffered by Wittgenstein against the concept of a private language and evaluates the counterarguments presented by his critics. These arguments encompass the future use argument, the interpretation argument, the stage-setting argument, the use argument, and the practice argument. Through a comprehensive analysis of these arguments, Wittgenstein substantiates the intrinsic unattainability of a private language. A privately defined word lacks the fundamental attributes of language, notably an established meaning, usability, prospective applicability, practical implications, interpretability, and a coherent framework governing the roles of its constituent elements. Ultimately, it is asserted that a private language cannot exist autonomously, separate from a public language.